Correlation of the Need for Orthodontic Treatment between the self-perception of Chilean adolescents aged 14 to 18 years and the dentist's diagnosis - Claudia Acevedo-Atala; José María Montiel-Company; Claudia Atala-Acevedo; Gilda Corsini-Muñoz; Víctor Beltrán-Varas; Alejandra Jans-Muñoz (Universidad de Concepción., 2021)
Background: To correlate the need for orthodontic treatment between the self-perception of Chilean adolescents from 14 to 18 years old with the observation of a dentist using the same assessment scale, as well as to determine if covariates such as gender, age and type of school influence the self-perception of the adolescent and the examiner. Material and Methods: Cross-sectional descriptive study of adolescents aged 14 to 18 years from public, subsidized and private schools in Temuco, Chile. The probability sample is stratified by course, from first to fourth year, a total of 414 students participated, according to the eligibility criteria. The photographic score of the aesthetic component (AC) of the Index of Orthodontic Treatment Need (IOTN) was used. The statistical analysis of the data was performed with the SPSS Statistics program v.23. Results: 94.9% of the adolescents perceived themselves as having good aesthetics. The examiner considered that 77% presented this condition, p<0.00. Males perceived themselves better than females. At age 15, 1.7% of students considered themselves to have poor aesthetics, p<0.01. From the examiner's perspective, aesthetics are related to type of school, p<0.00. Conclusion: Adolescents perceive themselves better aesthetically than do the evaluators. The school type factor, according to the IOTN-AC examiner, shows a higher proportion of students with no need for orthodontic treatment in private schools, and a threshold need in municipal and subsidized institutions.